2022
DOI: 10.3389/fpls.2022.918211
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Diversity of Ascochyta fabae Populations in Southern Australia

Abstract: Ascochyta fabae Speg. is a serious foliar fungal disease of faba bean and a constraint to production worldwide. This study investigated the phenotypic and genotypic diversity of the A. fabae pathogen population in southern Australia and the pathogenic variability of the population was examined on a differential set of faba bean cultivars. The host set was inoculated with 154 A. fabae isolates collected from 2015 to 2018 and a range of disease reactions from high to low aggressiveness was observed. Eighty perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…(2015) in their study on Syrian populations. In contrast, Blake et al. (2022) reported an equal ratio of MAT1–1 and MAT1–2 in a collection of 311 isolates of A. fabae from South Australia.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…(2015) in their study on Syrian populations. In contrast, Blake et al. (2022) reported an equal ratio of MAT1–1 and MAT1–2 in a collection of 311 isolates of A. fabae from South Australia.…”
Section: Discussionmentioning
confidence: 88%
“…(2015) showed that 1:1 ratio could not be rejected for two populations of A. fabae from Syria although a random mating hypothesis was rejected in these populations. In contrast, a study conducted on 311 isolates of A. fabae collected between 1991 and 2018 in South Australia by Blake et al. (2022) showed an equal ratio of MAT1–1 and MAT1–2.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Therefore, some researchers have suggested the existence of races of the pathogen, but this is not fully documented (Díaz-Ruiz et al, 2009;Tivoli et al, 2006). Rather, in the A. fabae population, pathogenicity groups are identified according to the severity of disease symptoms caused by isolates on a set of cultivars with different resistance (Blake et al, 2022). Sexual reproduction allows the emergence of new combinations of virulence, which is associated with the possibility that the pathogen responds to the selection exerted by the introduction of host resistance genes (Ozkilinc et al, 2015;Rubiales and Trapero-Casas, 2002).…”
Section: Introductionmentioning
confidence: 99%